2021
DOI: 10.1080/2162402x.2021.1944554
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in the immune microenvironment of oral potentially malignant disorders reveal an unexpected association of M2 macrophages with oral cancer free survival

Abstract: Understanding the dynamics of the immune microenvironment is critical to the development of immuno-based strategies for the prevention of oral potentially malignant disorders transformation to oral squamous cell carcinoma (OSCC). We used laser capture microdissection and RNA-sequencing to profile the expression of 13 matched pairs of epithelial versus stromal compartments from normal mucosa, hyperplasia, dysplasia, and invasive tumors in the 4-nitroquinolein (4-NQO) murine model of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(46 reference statements)
2
15
0
1
Order By: Relevance
“…Bouaoud et al. used immune cell deconvolution and enrichment algorithms for RNAseq as well as immunohistochemistry on OPL to observe that M2 macrophages were associated with dysplasia and OSCC even though 3 M2 TAM signatures were associated with better oral cancer-free survival ( 34 ). By contrast, Mori et al.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouaoud et al. used immune cell deconvolution and enrichment algorithms for RNAseq as well as immunohistochemistry on OPL to observe that M2 macrophages were associated with dysplasia and OSCC even though 3 M2 TAM signatures were associated with better oral cancer-free survival ( 34 ). By contrast, Mori et al.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“…However, some groups indicate that TAMs may inhibit OPL regardless of M1 or M2 phenotype. Bouaoud et al used immune cell deconvolution and e n r i c h m e n t a l g o r i t h m s f o r R N A s e q a s w e l l a s immunohistochemistry on OPL to observe that M2 macrophages were associated with dysplasia and OSCC even though 3 M2 TAM signatures were associated with better oral cancer-free survival (34). By contrast, Mori et al demonstrated that the M2 canonical marker CD163 may identify TAMs with an inflammatory rather than immunosuppressive phenotype.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“… 46–50 Moreover, recent studies have presented convincing evidence that copious M2 macrophages in TME are significantly associated with deteriorated OS in HNSCC patients. 51–55 Through establishing a co-culture system using CM of FN1-deficient HNSCC cells, we observed an obvious decrease in the expression of M2 macrophage markers. These results suggest that FN1 may induce macrophage M2 polarization in HNSCC.…”
Section: Discussionmentioning
confidence: 89%
“…Mice were randomly assigned into two cages in each group for collecting feces and recording survival. We randomly divided BABL/c male mice into an experimental group ( n = 20) provided with drinking water containing 100 mg/L 4NQO (sigma, United States) and into a control group ( n = 20) provided with drinking water without 4NQO ( Bouaoud et al, 2021 ). Five mice were randomly sacrificed every 4 weeks, continuously for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%